2018
DOI: 10.3389/fpubh.2018.00285
|View full text |Cite
|
Sign up to set email alerts
|

Demand Side Factors Associated With Quality Antenatal Care Services: A Case Study of Lusaka District, Zambia

Abstract: Background: The quality of antenatal care (ANC) a woman receives during pregnancy is crucial to both the child and the mother's life. It has been established that providing high-quality ANC can save lives and has a positive impact on postnatal health care services. However, the quality of ANC in Zambia requires attention as maternal and neonatal mortality rates are still unacceptably high with Lusaka district not being left out of the problem.Methods: Using a cross-sectional study design, the main aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 13 publications
4
27
2
Order By: Relevance
“…These findings were corroborated by a study that showed how spouses or partners can influence women to participate in ANC [ 28 ], producing better results by ensuring that women attend their ANC consultations and receive quality services. Yet, these results also contrast with those reported by other authors [ 29 ].…”
Section: Discussioncontrasting
confidence: 99%
“…These findings were corroborated by a study that showed how spouses or partners can influence women to participate in ANC [ 28 ], producing better results by ensuring that women attend their ANC consultations and receive quality services. Yet, these results also contrast with those reported by other authors [ 29 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Our study revealed that the proportion of adequately received ANC contents was 28%. This result is in line with a study conducted in LMICs ranging from 10 to 50% in Jordan, Nigeria, Nepal, Colombia, and Haiti 49 and studies in Bangladesh (22%), 20 Zambia (29%), 16 but lower than studies done in Ghana (48%), 23 Myanmar (58%), 41 Zambia (47.1%), 50 and higher than studies in Nigeria (7%), 22 twenty countries in sub-Saharan Africa (5%). 51 The slow progress towards maternal and newborn survival due to ineffective care may be attributable to the gaps between globally recommended coverage indicators measuring contacts rather than the actual content.…”
Section: Discussionsupporting
confidence: 91%
“…In the same way, previous studies showed that as education increases, number of received ANC content also increases. 9 , 22 , 42 , 50 , 51 , 55 Relatively affordable and accessible health information for educated women compared to those who never attended schools may explain the associations. 56 Furthermore, education fosters maternal healthcare awareness, appropriate need-based services utilization, 17 , 20 , 57 household maternal decision-making ability, 57 autonomy on their health, 58 new values and attitudes that favor modern health care.…”
Section: Discussionmentioning
confidence: 99%
“… 44 , 47 The quality of ANC services does not depend solely on the timing and number of ANC visits, and the physical examination but also on the type and quantity of interventions, such as maternal height, urine examination, examining the total blood count, measurement of blood pressure, general physical examination, iron supplementation, administration of folic acid tablets, voluntary counselling and testing for HIV, prevention of maternal transmission of HIV to the infant, administering antimalarial drugs, providing isoniazid prophylaxis against tuberculosis and other interventions. 48 , 49 Our study confirms the findings in other studies that showed that ANC interventions though important, were not mentioned as causes of pregnant women’s dissatisfaction with ANC services.…”
Section: Discussionsupporting
confidence: 89%